THE ROLE OF MANAGEMENT ACCOUNTANTS IN HUMAN-MACHINE COLLABORATION: EMERGING COMPETENCIES AND ETHICAL CHALLENGES - Christina Sososutiksno; Tiara Dwi Cahyani Yunus; Resty Hairunnisya Pulu Hattumena (Adisam Publisher, 2026)
The development of digital technology, particularly intelligence and automation systems, has transformed the role of management accountants in decision-making and information management. This study aims to examine the role of management accountants in human-machine collaboration, focusing on emerging competencies and associated ethical challenges. Using a literature review method, this study collected and analyzed recent research, scholarly articles, and industry reports to identify new skills required by management accountants, including advanced analytical skills, data literacy, and an understanding of technology ethics. The results indicate that human-machine collaboration requires management accountants not only to master technical aspects but also to possess critical capacity to assess decisions generated by automated systems. Furthermore, ethical challenges arise from potential algorithmic bias, data confidentiality, and professional responsibility in the use of AI. This study provides a conceptual framework for understanding the transformation of the role of management accountants in the digital era and emphasizes the importance of integrating technical and ethical competencies in professional practice.